Quality of life and stigma among persons affected by leprosy or buruli ulcer in Nigeria: a community-based cross-sectional study - Amaka Esmai-Onyima; Ngozi Ekeke; Ifeyinwa Ezenwosu; Edmund N. Ossai; Chinwe Eze; Francis Chinawa; Obiora Iteke; Precious Henry; Charles Nwafor; Ngozi Murphy-Okpala; Martin Njoku; Anthony O. Meka; et al. (BMC Public Health)
Abstract Introduction Skin Neglected tropical diseases including leprosy and Buruli ulcer cause aesthetic and functional impairments due to late detection of the diseases. This study assessed the quality of life and stigma among persons affected by leprosy or Buruli ulcer in Nigeria. Methods This was a community-based cross-sectional study. It involved 635 persons affected by leprosy or Buruli ulcers who were purposively selected from the endemic local government areas in six Southern States of Nigeria. The SARI Stigma Scale was used to assess stigma while the WHOQOL-BREF questionnaire was used to determine the Quality of life. Chi-square test, Correlation analysis, Mann Whitney U, Kruskal Wallis tests and multivariate analysis using binary logistic regression analysis were used in the study. The level of statistical significance was determined by a p-value of < 0.05. Results The mean age of the respondents was 43.8 ± 17.0years. A higher proportion of the respondents, 78.9% were affected by leprosy. Less than one-third of the respondents, 29.3% had good quality of life. The mean overall stigma score was significantly higher for leprosy patients when compared with BU, (p = 0.042). There was a strong negative correlation between overall stigma and overall quality of life, (n = 635, r=-0.530, p < 0.001). There was a strong positive correlation between overall social support and overall quality of life, (n = 635, r = 0.558, p < 0.001). Predictors of good quality of life included having no formal education, (AOR = 0.4, 95%CI: 0.2–0.7), being unemployed, (AOR = 0.4, 95%CI: 0.2–0.7), having vocational training, (AOR = 2.1, 95%CI: 1.1–4.1), being affected by leprosy, (AOR = 4.3, 95%CI: 2.3–8.1) and having poor social support, (AOR = 0.1, 95%CI: 0.05–0.2). Conclusion The quality of life of the individuals decreases as the level of stigma increases. Thus, the need to continue community health education campaigns to change the existing stereotypes about the diseases and provide strong social support for the affected individuals.